2002
DOI: 10.1007/s00586-001-0360-z
|View full text |Cite
|
Sign up to set email alerts
|

Fate of the transpedicular intervertebral bone graft after posterior stabilisation of thoracolumbar fractures

Abstract: The authors present a retrospective clinical and radiological study addressing the outcome after posterior stabilisation of thoracolumbar fractures with intervertebral fusion via transpedicular bone grafting. The study included computed tomographic (CT) scan after implant removal for analysis of the intervertebral fusion and incorporation of the intervertebral bone graft and its influence on postoperative re-kyphosing. Twenty-nine patients with acute fractures of the thoracolumbar spine, treated between 1988 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 35 publications
5
37
0
3
Order By: Relevance
“…The average age (43.1 years) and the distribution of gender (58% men) are well in agreement with the descriptions in other studies [6,10,[36][37][38]. Falls from a great height are the most frequent cause of injury, followed by road accidents [10,[36][37][38][39].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The average age (43.1 years) and the distribution of gender (58% men) are well in agreement with the descriptions in other studies [6,10,[36][37][38]. Falls from a great height are the most frequent cause of injury, followed by road accidents [10,[36][37][38][39].…”
Section: Discussionsupporting
confidence: 90%
“…This value is just little lower than the score reduction of 24.1 reported by Knop et al [34] for patients treated with an internal fixator and bone chips. The score reduction obtained is similar to those found by previous [10,17,38] studies using other questionnaires. Briem et al [44] reported about a relevant long-term impairment in patients' quality of life after dorso ventral stabilization of thoracolumbar fractures and concluded pain as the most compromising factor being related as well to the severity of the injury and as to the operation itself.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Fractures of the thoracolumbar spine are major injuries that often require surgical intervention and are known to have an important impact on the long-term outcome after trauma [1]. Most of the studies on the outcome after fractures of the thoracolumbar spine focused on radiological parameters, return to work, activity, and pain [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] without consideration of specific HRQoL outcome measures. Assessment of HRQoL after thoracolumbar fractures with generic instruments such as Short Form-36 health survey (SF-36) has only been reported in a few works [1,[17][18][19][20], which are all limited by the low number of the used HRQoL instruments.…”
Section: Introductionmentioning
confidence: 99%